Association between interleukin- 6 promoter haplotypes and aggressive periodontitis - Luigi Nibali (Blackwell Synergy, 2008)
Background: Interleukin-6 (IL-6) polymorphisms have been shown to affect IL-6 promoter activity. This study investigated the possible role of IL-6 genetic polymorphisms and haplotypes in the predisposition to aggressive periodontitis (AgP). Material and Methods: A case–control association study on 224 AgP patients and 231 healthy controls was performed in order to detect differences in genotype distributions of five single nucleotide polymorphisms (SNPs) located in the promoter region of the IL-6 gene. Results: The IL-6 1363 polymorphism was associated with a diagnosis of AgP in subjects of all ethnicities (p50.006, adjusted logistic regression). The 1480 SNP was associated with LAgP in subjects of all ethnicities (p50.003). The 1480 and 6106 polymorphisms were associated with Localized AgP in Caucasians (n524) (p50.007 and 0.010, respectively). Haplotypes determined by the 1363 and 1480 polymorphisms were also associated with LAgP (p50.001) in Caucasians. Conclusions: This study supports the hypothesis of a link between IL-6 genetic factors and AgP and highlights the importance of two IL-6 polymorphisms ( 1363 and 1480) in modulating disease phenotype and susceptibility.